[Queen's Park Savannah, Trinidad] - (:unkn) unknown (My University, 2009)
A view of the Queen's Park Savannah with trees littering the fields and on the right, the road that circles the savannah.
Colour: Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Trees--Trinidad and Tobago; Roads--Trinidad and Tobago; Roads--Guard fences; Fences--Trinidad and Tobago; Electric lines--Trinidad and Tobago; Overhead electric lines--Trinidad and Tobago; Electric power distribution--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Pitch Walk, The; Queen's Park Savannah (Port of Spain)